Cellular Ecophysiology of Microbe: Hydrocarbon and Lipid Interactions (Handbook of Hydrocarbon and Lipid Microbiology, 2018)
This book assembles concisely written chapters by world-leaders in the field summarizing recent advances in understanding microbial responses to hydrocarbons. Subjects treated include mechanisms of sensing, hydrocarbon tolerance and degradation as well as an overview on hydrophobic modification of biomolecules. Other chapters are dedicated to issues related to the reduced bioavailability of hydrocarbons, which differentiates this class of compounds form many others, but which of central importance to understand the ecophysiological consequences. This book should be standard literature in any laboratory working in this area.